Pathology and Pathobiology of Pulmonary Hypertension - Guignabert, Christophe; Dorfmuller, Peter (Seminars in Respiratory and Critical Care Medicine, 2013)
Pulmonary hypertension is a devastating, life-threatening disorder with no curative options, characterized by elevated pulmonary vascular resistance and secondary right ventricular failure. Although the etiologies of pulmonary arterial hypertension are multiple and its pathogenesis is complex, there is growing evidence that inflammation, endothelial dysfunction, aberrant vascular wall cell proliferation, as well as mutations in the bone morphogenetic protein receptor type 2 gene play a crucial role in triggering pathological vascular remodeling. The present article outlines the current understanding of this disease from the point of view of pathology and pathobiology.
Keywords: pulmonary arterial hypertension; pulmonary vascular remodeling; endothelial dysfunction; cellular cross talk; inflammation; BMPR2